Early congenital syphilis: missed opportunities in a mother owing to many problems during pregnancy – a case report. (3rd April 2022) - Krishnapura Lakshminarayana, Shilpa; Devadas, Sahana; Bharath, K.; Kariyappa, Mallesh; Byadarahalli Keshavamurthy, Bindushree; S. Bagewadi, Megha; Veeranna Sajjan, Sushma; Vineet, Dadegal; Mohammed, Thanzir
ABSTRACT: Untreated syphilis in pregnancy can result in an adverse outcome for the fetus. A multigravida woman with a previously poor obstetric history of early neonatal death, abortion and stillbirth was admitted in labour in the 7th month of pregnancy. On admission, syphilis screening with the qualitative rapid plasma reagin (RPR) test was negative. The infant had macules on the chest, abdomen and extremities, desquamating bullous skin lesions on the palms and soles, bilateral cataracts, an enlarged liver and spleen, anaemia, thrombocytopenia and conjugated hyperbilirubinaemia. A quantitative RPR test in the infant was positive in a 1:64 dilution and was subsequently positive in the mother in a 1:16 dilution after congenital syphilis was diagnosed. The mother later reported the father's high-risk behaviour and her previous visits to healthcare facilities for genital ulcers. The quantitative RPR test in the father was positive in a 1:32 dilution, and the parents and infant were treated for syphilis. The case demonstrates the importance of timely identification of high-risk pregnant women, early screening, repetition of the non-treponemal test on diluted serum when a routine screening test is negative, proper advice from the laboratory regarding selection of the most appropriate tests, and screening with the treponemal test first (reverse) algorithm utilising an automated enzyme immunoassay/chemiluminescence assay for the initial screening in high-risk cases, even in resource-limited settings to prevent a missed diagnosis. Abbreviations: ANC, antenatal care; BPG, benzathine penicillin G; CS, congenital syphilis; CSF, cerebrospinal fluid; CIA, chemiluminescence assay; EIA, enzyme immunoassay; HIC: high-income countries; IgM, immunoglobulin M; LMIC, low- and middle-income countries; MTCT: mother-to-child transmission; NTT, non-treponemal test; POC, point of care; RPR, rapid plasma reagin; RST, rapid syphilis test; STI, sexually transmitted infections; TT, treponemal test; TPHA, Treponema pallidum haemagglutination assay; VDRL, venereal disease research laboratory; WHO, World Health Organization.